Randomized Open Clinical Trial to Evaluate Netratarpana Efficacy in Elderly Patients with Primary Insomnia (Anidra) (Sciences of Pharmacy, 2023)
Primary insomnia is the most prevalent health problem among the elderly in India. It is linked to musculoskeletal disorders, cardiac disorders, Chronic Obstructive Pulmonary Disease (COPD), depression, and schizophrenia. The incidence rate of primary insomnia among the elderly is 5%, and the prevalence rate is 20% or more. With an increase in the geriatric population, this prevalence rate will increase further. In Ayurveda, Netratarpana is described as a treatment modality for insomnia, but it was not studied yet. The study aimed to evaluate the efficacy of Netratarpana in Anidra (primary insomnia). In this RCT, 70 patients with Primary insomnia were randomly divided into two groups. In group A (n=35), Netratarpana was performed for 14 days, and group B (n= 35) was given Jatamansi powder 5 g at night with buffalo milk for 14 days as a comparison. The follow-up was taken on the 7th, 14th, and 21st day. The assessment was done using the Insomnia Severity Index (ISI) with the addition of Ayurvedic parameters. A total of 49 (70%) patients have an average age of 59.3 ± 3 years. There were 50 (71.4%) males and 20 (28.6 %) females. The sleep pattern was disturbed among 7 (10%), delayed among 19 (27.1%), and disturbed and delayed among 44 (62.9%). We found both Netratarpana and Jatamansi powder are effective in inducing sleep and preventing awakening during the night with a p-value of <0.05. It can be concluded that Netratarpana is effective in managing Anidra (primary insomnia), but the stability of the results needs to be confirmed by further study.